tRNA-like structures of plant viral RNAs: conformational requirements for adenylation and aminoacylation. - Joshi, R L (1983)
Bromo- and cucumovirus RNAs contain a tRNA-like structure as an integral part of their genome. This structure is located at the 3' end of the viral RNA and is an acceptor of tyrosine. The 3' regions of representative viral RNAs have been sequenced and quite unorthodox secondary foldings have been proposed for these 3' ends. The question therefore remained as to how these structures could be recognized by tRNA-specific enzymes. We have established the minimum number of nucleotides from the 3' end of the brome mosaic virus and broad bean mottle virus RNAs required for the formation of structures recognized by the tyrosyl-tRNA synthetase and/or the tRNA nucleotidyltransferase. The results obtained delineate the length of the tRNA-like region, and indicate that the 5' region of the tRNA-like structure participates in the formation of the amino acid stem. This has led us to propose an 'L'-shaped secondary structure for these tRNA-like regions.